Preparation method of intermediate layer for all-solid-state lithium metal battery and all-solid-state lithium metal battery
By using the middle layer composed of nanochohicine black and dense metal layers in the full -solid lithium metal battery, the problem of poor contact and lithium branches crystal growth of the battery negative metal layer has significantly improved the cycle stability and magnification performance of the battery.
Patent Information
- Application Number
- CN202411268449.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-09-11
AI Technical Summary
During the cycle process, all-solid lithium metal batteries have poor negative interface contact, and lithium dendrites have caused short circuits, poor rate performance and short cycle life of the battery.
A method for preparing an intermediate layer for an all-solid-state lithium metal battery is adopted. The intermediate layer includes nano-Kotjen Black or its composite layer as the first material layer, and dense metal layers (such as Sn and Mg) as the second and third material layers. , prepared by ultrasonic dispersion and vacuum evaporation technology.
Effectively avoid direct contact with negative electrolytes and lithium metal poles, inhibit the growth of lithium branches, improve the cycle stability and magnification performance of the battery, and extend the cycle life of the battery.
Smart Images

Figure CN118841636B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of solid-state batteries, and specifically relates to a method for preparing an intermediate layer for an all-solid-state lithium metal battery and an all-solid-state lithium metal battery. Background Art
[0002] As an advanced battery technology, all-solid-state sulfide lithium metal batteries have significant advantages in energy density, safety and cycle life. Compared with liquid electrolytes, solid sulfide electrolytes have higher thermal stability, wider electrochemical window and lower self-discharge rate. They are considered to be one of the most promising solid electrolytes due to their high ionic conductivity at room temperature. Lithium metal has the lowest redox potential (-3.04 V compared to the standard hydrogen electrode), which enables the lithium metal negative electrode to produce a larger potential difference in the battery, thereby driving the battery to produce higher voltage and power. And it has an extremely high theoretical specific capacity (3860 mAh g -1 ), far exceeding the traditional graphite negative electrode (about 372mAh g -1 ), which means that the lithium metal negative electrode can store more energy and provide a higher energy density for the battery. In recent years, with the rapid growth of the new energy vehicle market and the potential demand in the field of energy storage, the requirements for battery performance (such as high energy density, high safety and long life performance) have been continuously improved. All-solid-state sulfide lithium metal batteries have broad development prospects. With the continuous advancement of technology, they are expected to become one of the important representatives of the next generation of battery technology.
[0003] However, all-solid-state sulfide lithium metal batteries also face a series of technical challenges. First, poor contact at the solid-solid interface will lead to extremely large interfacial impedance, affecting the transmission efficiency of lithium ions and batteries; second, the poor interfacial contact and poor electrochemical stability between the lithium metal negative electrode and the sulfide electrolyte will easily form a high-impedance SEI film and promote the growth of lithium dendrites. The increase in interfacial impedance leads to battery short circuit; third, the uneven lithium deposition at the negative electrode interface during the cycle causes the interface contact to deteriorate continuously, increasing the risk of lithium dendrite growth, especially under high load and high rate conditions, lithium dendrites may penetrate the solid electrolyte and cause the battery to short-circuit and fail.
[0004] In order to overcome the instability and dendrite growth problems at the interface between lithium metal anode and sulfide electrolyte, appropriate interface modification is required to improve the stability and cycle life of the battery. Summary of the invention
[0005] In view of the above-mentioned problems, the present invention provides a method for preparing an intermediate layer between a sulfide electrolyte and a lithium metal negative electrode and an all-solid-state lithium metal battery. The technical problem to be solved is the poor interface contact of the negative electrode during the cycle of the all-solid-state lithium metal battery, the growth of lithium dendrites leading to battery short circuit, poor rate performance and short cycle life.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is:
[0007] In a first aspect, the present invention proposes a method for preparing an intermediate layer for an all-solid-state lithium metal battery, wherein the intermediate layer comprises a first material layer, a second material layer and a third material layer arranged in sequence, wherein the first material layer is nano Ketjen black, or a composite layer of nano Ketjen black and an oxide filler, and the second material layer and the third material layer are both dense metal layers.
[0008] The preparation method of the intermediate layer includes the following processes: dispersing a certain mass of nano Ketjen black powder or nano Ketjen black powder and oxide filler, binder and dispersant in a certain mass of N-methyl-2-pyrrolidone (NMP), using ultrasound and stirring to disperse for at least 3 to 5 hours, uniformly coating the obtained slurry on the surface of aluminum foil, and vacuum drying to obtain a first material layer for standby use; using a vacuum evaporation device to successively evaporate a second material layer and a third material layer on the surface of the first material layer to obtain the intermediate layer.
[0009] Furthermore, the oxide filler is one of CoO, CuO, ZnO, SiO, Co3O4, and Al2O3.
[0010] Furthermore, the D50 of the oxide filler particles is 10-200 nm, preferably 30 nm.
[0011] Furthermore, the second material layer is one of the metals Sn, Sb, Ge, and Bi; and the third material layer is one of the metals Ag, Mg, Al, Zn, and In.
[0012] Furthermore, the binder is polyvinylidene fluoride (PVDF); and the dispersant is polyvinyl pyrrolidone (PVP).
[0013] Furthermore, the thickness of the first material layer is 2-8 μm; the thickness of the second material layer is 10-100 nm, preferably 50 nm; and the thickness of the third material layer is 100-500 nm, preferably 200 nm.
[0014] Furthermore, in the composite layer of nano Ketjen black and oxide filler, the ratio of nano Ketjen black to oxide filler is 1:3, and the contents of binder and dispersant account for 3% to 10% and 1% to 6% of the total solid mass, respectively.
[0015] Furthermore, the obtained slurry is evenly coated on the surface of aluminum foil, and dried at 100-120° C. in vacuum for 10-15 hours for later use.
[0016] In the second aspect, the present invention proposes an all-solid-state lithium metal battery, comprising a positive electrode, a solid electrolyte and a negative electrode, wherein the solid electrolyte is a sulfide solid electrolyte, the negative electrode is a lithium metal negative electrode, and an intermediate layer prepared by the preparation method as described above is arranged between the solid electrolyte and the negative electrode.
[0017] Compared with the prior art, the technical solution of the present invention has the following beneficial effects: (taking ZnO as the oxide filler, Sn metal as the second material layer, and Mg metal as the third material layer as an example for explanation, other metals or oxides can be selected to have the same effect)
[0018] 1. The thinner nano-Kojkin black layer in the intermediate layer can effectively avoid direct contact between the electrolyte and the lithium metal negative electrode, reduce side reactions, and the Li-Zn alloy generated by the reaction of ZnO and Li serves as a fast transmission channel for lithium.
[0019] 2. The high diffusion coefficient and dense Li-Mg can effectively regulate the lithium ion flux and inhibit the growth and penetration of lithium dendrites. The large volume expansion of the Li-Sn alloy layer after alloying can provide pressure inside to ensure good contact between the electrode interfaces.
[0020] 4. The intermediate layer has the advantages of thin thickness, light weight and low cost, and has significant advantages in improving battery safety, cycle stability, energy density and broadening the scope of application.
[0021] 5. The preparation process of the intermediate layer is simple, using the slurry and pole piece coating technology of traditional liquid lithium-ion batteries. The process technology is mature, which is conducive to large-scale production and ensures high production efficiency.
[0022] In summary, in order to solve the problem that the all-solid-state battery with lithium metal as the negative electrode and solid sulfide as the electrolyte seriously affects the charge and discharge performance of the battery due to the instability of the lithium metal / electrolyte interface, the intermediate layer prepared by the present invention is an ultra-thin, porous mixed ion and electron conductor applied between the electrolyte and lithium metal, which has the function of regulating lithium deposition, stripping uniformity and isolating the electrolyte / lithium metal interface to prevent side reactions. The first material layer of the intermediate layer (porous carbon layer or a composite layer of porous carbon layer and oxide) is used to isolate the electrolyte / lithium metal interface. Secondly, the porous carbon layer is a good buffer material. When the solid-state battery is assembled and composited, a large pressure needs to be applied. The porous carbon layer can prevent the interface from being damaged during the composite; the second material layer (plating metal 1) is alloyed with the deposited lithium after the battery is charged for the first time, and the volume expansion provides compressive stress between the pole pieces to ensure good contact between the pole piece interfaces and reduce the battery interface impedance. The third material layer (plating metal 2) is also alloyed with the deposited lithium. The alloy formed has the function of regulating the lithium ion flux and making lithium deposited uniformly, so the intermediate layer can effectively improve the interface problem of the negative electrode of the all-solid-state battery.
[0023] When assembling an all-solid-state lithium metal battery, the middle layer is first coated on the surface of the aluminum foil with a slurry using aluminum foil as a carrier. After drying and evaporation, it is compounded with the positive electrode-electrolyte at an appropriate pressure, and then the aluminum foil is peeled off to obtain the positive electrode-electrolyte-middle layer. The negative electrode uses a lithium-stainless steel strip (composite of lithium metal foil and stainless steel strip, lithium metal foil as the negative electrode of the battery, and stainless steel strip as the negative electrode current collector). The lithium-stainless steel strip is compounded with the positive electrode-electrolyte-middle layer under a certain pressure to obtain an all-solid-state lithium metal battery with an intermediate layer (positive electrode-electrolyte-middle layer-lithium-stainless steel strip). Therefore, the middle layer is a regulating layer placed between the electrolyte and the lithium negative electrode, which can not only isolate the electrolyte and lithium metal interface, but also conduct lithium and electrons between the negative electrode and the electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a schematic structural diagram of an intermediate layer for an all-solid-state lithium metal battery of the present invention;
[0025] Figure 2 The rate performance of the soft-pack battery assembled using the intermediate layer prepared in Example 1 is tested;
[0026] Figure 3 The cycle performance of the soft-pack battery assembled using the intermediate layer prepared in Example 1 is tested;
[0027] Figure 4 The rate performance of the soft-pack battery assembled using the intermediate layer prepared in Example 2 is tested;
[0028] Figure 5It is the cycling performance of the lithium metal soft pack battery tested without the use of an intermediate layer;
[0029] Figure 6 These are the charge and discharge curves of the 1st, 3rd, 5th, and 7th cycles of a lithium metal soft-pack battery assembled without an intermediate layer;
[0030] Figure 7 It is the surface impedance data of the soft-pack batteries assembled in Example 1 and Example 2 and the comparative example tested at room temperature and 2~10MPa conditions. DETAILED DESCRIPTION
[0031] To make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described in detail below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention.
[0032] Embodiment 1:
[0033] 752 mg of nano Ketjen black powder, 480 mg of PVDF (5 wt% solution) and 1200 mg of PVP (2 wt% solution) were dispersed in 13568 mg of NMP by ultrasonic stirring for 3 h, and the obtained slurry was coated on the surface of aluminum foil, and dried at 100 ° C in vacuum for 12 h before use. The intermediate layer was obtained by successively evaporating 50 nm Sn and 200 nm Mg on the surface using a vacuum evaporator.
[0034] Embodiment 2:
[0035] 1104 mg of ZnO nanoparticle powder, 368 mg of nano Ketjen black powder, 960 mg of PVDF (5 wt% solution) and 4000 mg of PVP (2 wt% solution) were dispersed in 16425 mg of NMP by ultrasonic stirring for 3 hours, and the obtained slurry was coated on the surface of aluminum foil, dried at 100 ° C in vacuum for 12 hours and then used. The intermediate layer was obtained by successively evaporating 50 nm Sn and 200 nm Mg on the surface using a vacuum evaporator.
[0036] Embodiment 3:
[0037] 1104mg of Al2O3 nanoparticle powder, 368mg of nano Ketjen black powder, 960mg of PVDF (5wt% solution) and 4000mg of PVP (2wt% solution) were dispersed in 16425mg of NMP by ultrasonic stirring for 3h, and the obtained slurry was coated on the surface of aluminum foil, dried at 100℃ in vacuum for 12h and then used. The intermediate layer was obtained by successively evaporating 50nmSn and 200nmMg on the surface using a vacuum evaporator.
[0038] Embodiment: 4:
[0039] 1104 mg of ZnO nanoparticle powder, 368 mg of nano Ketjen black powder, 960 mg of PVDF (5 wt% solution) and 4000 mg of PVP (2 wt% solution) were dispersed in 16425 mg of NMP by ultrasonic stirring for 3 hours, and the obtained slurry was coated on the surface of aluminum foil, dried at 100 ° C in vacuum for 12 hours and then used. 50 nm Sb and 200 nm Ag were successively evaporated on the surface by vacuum evaporation apparatus to obtain the intermediate layer.
[0040] Comparative Example:
[0041] No intermediate layer is used, lithium metal is directly used as the negative electrode, and the assembly method is consistent with the battery of the embodiment.
[0042] Battery assembly method:
[0043] Embodiment: The dry-process positive electrode sheet, the sulfide electrolyte membrane, and the intermediate layer are stacked together in order, and an isostatic pressing device is used to apply a pressure of 500-800 MPa for compounding, and then a lithium-stainless steel strip is attached to the surface of the intermediate layer, and then a pressure of 20-50 MPa is used for compounding.
[0044] Comparative Example: No intermediate layer is added, and the assembly method and sequence are the same as above.
[0045] Legend:
[0046] Figure 1 To illustrate the structural schematic diagram of an intermediate layer for an all-solid-state lithium metal battery of the present invention, the structure is composed of three material layers, and the first, second and third material layers are Ketjen black layer (or a mixed layer of Ketjen black and ZnO), metal Mg, and Sn plating layers, respectively.
[0047] In terms of rate performance, Figure 2 , 4 It can be seen from the figure that the soft-pack battery with an intermediate layer can adapt to different charge and discharge rates (0.1C~1C). Figure 3It can be seen that at a charge and discharge rate of 0.5C, the discharge capacity is stable at more than 140mAh / g, and can be cycled stably for more than 100 cycles without any short circuit (such as Figure 3 ). Lithium metal batteries without an intermediate layer Figure 5 It can be seen from the data that it can only be cycled at a very low rate (0.04C), and a soft short circuit occurs at the 7th cycle, and the discharge specific capacity decreases sharply (such as Figure 6 ), the battery fails and cannot continue to charge or discharge.
[0048] Under the same battery conditions of room temperature and 5MPa stacking pressure, the impedance was tested and the data was fitted and calculated to obtain the surface impedance (such as Figure 7 As shown in the figure, the results show that the surface impedance of the lithium metal battery using the intermediate layer, that is, Example 1 and Example 2, is only 200Ωcm 2 , 40Ωcm 2 It is worth noting that after the oxide filler is added to the first material layer, the surface impedance of the battery at room temperature is significantly smaller, while the surface impedance of the lithium metal negative electrode battery without the intermediate layer reaches 3000Ωcm 2 . Therefore, the use of the intermediate layer can effectively inhibit the growth of lithium dendrites in lithium metal batteries, improve the battery coulomb efficiency, and extend the cycle life of the battery. The soft-pack batteries of Examples 3 and 4 also have a smaller impedance close to that of Examples 1 and 2, can be cycled at different rates (0.1~1C), and have good cycle stability (stable charge and discharge at a rate of 0.5C, with a discharge specific capacity of about 140mAh / g) and cycle life (more than 100 cycles).
[0049] In summary, the preparation of the intermediate layer of the embodiment of the present invention is to evenly coat the slurry mixed with nano Ketjen black (or nano Ketjen black and ZnO nanoparticles), a binder and a dispersant on the aluminum foil, and then use vacuum evaporation technology to evaporate a composite coating of metals such as Sn and Mg on its surface after drying. Ketjen black, as the main structure of the intermediate layer, can effectively block lithium metal and sulfide electrolytes to avoid the occurrence of side reactions of direct contact. The ZnO in Ketjen black can undergo an oxidation-reduction reaction with lithium, and the generated Zn reacts with Li to form a Li-Zn alloy, which is conducive to the rapid transmission of lithium in the intermediate layer and improves the reaction rate and energy conversion efficiency of the battery. The Li-Mg and Li-Sn alloys generated after the metal Mg and Sn are alloyed with Li have high lithium affinity and lithium diffusion coefficient, can regulate the uniform deposition and diffusion of lithium on the negative electrode side, inhibit the growth of lithium dendrites, and improve the battery charge and discharge efficiency. In addition, the large volume change (260%) after Li and Sn are alloyed can provide pressure between the electrode interfaces to ensure good contact.
[0050] Poor contact between solid phase interfaces is a common problem of solid-state batteries. Poor contact is bound to cause uneven lithium deposition from the positive electrode. In order to improve the problem of poor contact between solid phase interfaces, when the intermediate layer provided in the present invention is in effect, the third material layer (Mg as an example) provided is to alloy with the deposited lithium to form a Li-Mg alloy with a high diffusion coefficient and high lithium affinity, adjust the subsequent lithium flux deposited, and regulate the uniform deposition of lithium. When lithium continues to be transmitted downward, it will react with the second material layer (Sn as an example) provided to form a Li-Sn alloy. After Sn reacts with lithium metal alloying, the volume will expand violently to more than twice the original, which can provide considerable compressive stress between the negative electrode interfaces to ensure good contact. Secondly, in order to buffer the large volume expansion and prevent interface damage caused by local stress concentration, a first material layer (porous carbon layer) is provided below it, which is formed by polyvinylidene fluoride bonding nanocarbon particles to each other through van der Waals forces to form a porous carbon layer. When subjected to interfacial stress, the porosity shrinks, buffers the interfacial stress and has high elasticity, which is an excellent buffer layer. Moreover, the mixed oxide filler (ZnO) in the porous carbon layer is to undergo a replacement reaction with the lithium metal deposited downward to generate an alloy (Li-Zn alloy) with a high lithium diffusion coefficient. When the battery is discharged, the lithium metal in the negative electrode can be replenished back to the positive electrode in time, thereby improving the battery's charge and discharge efficiency. In addition, the position sequence of the first, second, and third material layers cannot be changed at will. First, the third material layer must be used to evenly deposit lithium ions, and then the second material layer reacts to provide compressive stress, and finally the first material layer buffers the stress. Therefore, the technical solution of the present invention solves the above technical problems very well.
[0051] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing an intermediate layer for an all-solid-state lithium metal battery, characterized in that: The intermediate layer includes a first material layer, a second material layer and a third material layer arranged in sequence, the first material layer is a nano Kejen black layer or a composite layer of nano Kejen black and an oxide filler, the second material layer and the third material layer are both dense metal layers; the metal of the second material layer is one of Sn, Sb, Ge, and Bi; the metal of the third material layer is one of Ag, Mg, Al, Zn, and In; the oxide filler is one of CoO, CuO, ZnO, SiO, Co3O4, and Al2O3; The preparation method comprises the following processes: dispersing a certain amount of nano Ketjen black powder or nano Ketjen black with oxide filler, binder and dispersant in a certain amount of NMP, dispersing for a period of time by ultrasonic and stirring, uniformly coating the obtained slurry on the surface of aluminum foil, and vacuum drying to obtain a first material layer for standby use; using a vacuum evaporation device to successively evaporate a second material layer and a third material layer on the surface of the first material layer to obtain the intermediate layer; The intermediate layer is arranged between the solid electrolyte and the negative electrode.
2. The method for preparing an intermediate layer for an all-solid-state lithium metal battery according to claim 1, characterized in that: The D50 of the oxide filler particles is 10-200 nm.
3. The method for preparing an intermediate layer for an all-solid-state lithium metal battery according to claim 1, characterized in that: The binder is PVDF; the dispersant is PVP.
4. The method for preparing an intermediate layer for an all-solid-state lithium metal battery according to claim 1, characterized in that: The thickness of the first material layer is 2-8 μm; the thickness of the second material layer is 10-100 nm; and the thickness of the third material layer is 100-500 nm.
5. The method for preparing an intermediate layer for an all-solid-state lithium metal battery according to claim 1, characterized in that: The obtained slurry is evenly coated on the surface of aluminum foil, and dried at 100-120°C in vacuum for 10-15h before use.
6. An all-solid-state lithium metal battery, characterized in that: It comprises a positive electrode, a solid electrolyte and a negative electrode, wherein the solid electrolyte is a sulfide solid electrolyte, the negative electrode is a lithium metal negative electrode, and the intermediate layer prepared by the preparation method according to any one of claims 1 to 5 is arranged between the solid electrolyte and the negative electrode.
Citation Information
Patent Citations
Lithium battery and preparation method and application thereof
CN111435756A
Lithium solid battery
US20190051933A1